Adopted transgender subjects are overrepresented and have a different psychosocial profile than their non-adopted counterparts: A case-control study - Iris Yaish; Yona Greenman; Karen M. Tordjman (PLoS ONE, 2025)
Background The factors driving the global increase in the number of transgender individuals remain unclear. It has been suggested that early-life events may interact with biological predispositions, yet little research has explored specific early-life circumstances that might contribute to gender incongruence. One such factor is adoption, as a few pediatric gender identity clinics have reported an overrepresentation of adoptees. However, no study has systematically examined whether this trend extends to adult transgender health centers, nor has the psychosocial profile of adopted transgender individuals been characterized in adulthood. Aims and methods This retrospective study was conducted in two phases to evaluate the prevalence and characteristics of adoptees among adult transgender patients seeking gender-affirming therapy. In Phase 1, we analyzed a cohort of 671 new adult subjects presenting between 2015 and 2021. In Phase 2, the nested case-control analysis, the 15 adoptees identified were matched in a 1:4 ratio with non-adopted controls based on age, assigned sex at birth, and presentation timing. Data on demographics, psychosocial factors, psychiatric diagnoses, and parental support were extracted from electronic records, and augmented by telephone interviews when needed. Results Adoptees constituted 2.2% of the clinic population, an order of magnitude higher than the national rate (P < 0.0001), with an unprecedented assigned-female-at-birth (AFAB) ratio of 73.3%. After matching, 60% of adoptees had at least one psychiatric co-morbidity, almost twice the rate of non-adopted controls (OR = 3.23, 95% CI: 1.02–10.21, P = 0.042). Despite coming from higher socioeconomic status homes (P < 0.001), adoptees had lower odds of achieving college education (P = 0.031), and receiving full parental support for transition (OR = 0.20, 95% CI: 0.05–0.71, P = 0.015). Notably, 28.6% of adoptees had attempted suicide vs 3.3% of non-adopted controls (OR = 11.6, 95% CI: 1.87–71.97, P = 0.01). Conclusions Adopted transgender individuals represent a vulnerable subgroup within the transgender population, characterized by unique psychosocial challenges. Our findings underscore the importance of tailored interventions and heightened support within transgender health clinics for adoptees seeking gender-affirming therapy. Further research is warranted to elucidate the interplay of adoption, biological predispositions, and social factors in the development of gender incongruence.